Sorotan literatur perbandingan Gagasan Sastera Islami Sayyid Sayyid `Abd al-Raziq dan Mohd Affandi Hassan - Mohd Adi Amzar Muhammad Nawawi,; Zulkarnain Mohamed,; Pabiyah Toklubok @ Hajimaming, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
Difference of views in understanding the idea of Islamic literature and criticism involves two different cultures often occur in the field of comparative literature world. Yet despite the differences and inequalities, still no agreement reached involving key issues in the discussion of the concept of Islamic literature. Thus, this paper aims to highlight the previous studies related to the ideas, theories and principles of Islamic literature, the examples of comparative literature study and leaders thought. Analysis of the literature is conducted to find justification for the study and comparison of ideas on the need of dismantling the Islamic literature involving two selected leaders, Sayyid Sayyid `Abd al-Raziq and Mohd Affandi Hassan. This is a qualitative study based on applied content analysis method. This literature review finds that the application of this comparative study is able to find the special formula in identifying similarities and differences in the concept of Islamic literature and criticism involving the two leaders while providing enlightenment to the players in this field.